YAP1 negatively regulates chondrocyte differentiation partly by activating the β-catenin signaling pathway. (June 2017) - Yang, Beining; Sun, Hualing; Song, Fangfang; Yu, Miao; Wu, Yanru; Wang, Jiawei
Abstract: YAP1 (Yes-associated protein 1) transcriptional coactivator is a downstream gene of the Hippo signaling pathway, which controls cell proliferation and differentiation. YAP1 plays a significant role in the regulation of cartilage and bone development. However, the molecular mechanism by which YAP1 regulates chondrocyte differentiation remains to be elucidated. Immunofluorescent staining was used to visualize the localization of YAP1 expression in the mouse chondroprogenitor ATDC5 cell line. ATDC5 cells with lentivirus-vector-mediated YAP1 overexpression and knockdown were established. The differentiation abilities were examined by real-time quantitative PCR and two staining methods The expression levels of sex-determining region Y-type high mobility group box protein (SOX9) and key proteins in the Wnt/β-catenin pathway were analyzed by Western blot. The Dickkopf-1 (Dkk1) and small interfering RNA (siRNA) of β-catenin were used for further study. The YAP1 protein was mainly expressed in the nucleus of ATDC5 cells. YAP1 overexpression enhanced chondrocyte proliferation but inhibited chondrocyte differentiation, which were contrary to the findings of the YAP1-knockdown group. Moreover, YAP1 overexpression activated Wnt/β-catenin signaling pathway. Treatment with exogenous DKK1 and β-catenin siRNA partially recaptured the effects of YAP1 overexpression on ATDC5 cell differentiation. Taken together, our study suggested that YAP1 attenuated ATDC5 cell chondrogenic and hypertrophic differentiation. We also demonstrated that YAP1 exerted its effect on the chondrocyte differentiation by activating the Wnt/β-catenin signaling pathway.